Looking towards policies supporting biofuels and technological change: Evidence from France. (October 2018) - Doumax-Tagliavini, Virginie; Sarasa, Cristina
Abstract: The increasing constraints on crude oil resources contribute to the emergence of liquid biofuels as an alternative for road transport fuels. The European Union (EU) Parliament called for a 7% limit on crop-based biofuels by 2030 and proposed increasing the incorporation target for advanced biofuels, within the proposals under discussion in relation to the post-2020 EU Renewable Energy Directive (RED II) by 2021–2030. The main objective of this work is to assess the economic impacts of the EU Parliament's decision concerning first generation biofuels. We also determine the conditions under which advanced biofuels could become available by examining the evolution of oil prices and public subsidies. We employ a recursive dynamic computable general equilibrium (CGE) model calibrated on the French economy. Advanced biofuels are modelled as latent technology and we include biofuel by-products. Our simulations provide guidelines for public decision-makers to design alternative fiscal policies to support biofuels in a context of regulatory uncertainty. Highlights: Economic impacts of first- and second-generation biofuel are evaluated. Conditions under which advanced biofuels could become available sooner. Latent technology is modelled using a logistic schedule in a dynamic CGE model.